Isolasi dan Karakterisasi Flavonoid dari Daun Kapuk (Ceiba pentandra L.) - Putri Diana; Nazulis Z; Sri Benti Etika (Departemen Kimia FMIPA UNP, 2013)
Have been done the isolation of flavonoids from the leaves of the kapok (Ceiba pentandra L.) in Chemical Research Laboratory, Faculty of mathematics ande Natural Sciences of the State University of Padang. This research aims to isolate and to know the characteristics of the flavonoid compounds from the leaves of kapok. Method of insulationus is maceration with methanol, followed by oil with n-hexane and ethyl acetate. Separation of the ethyl acetate fraction by coloumn chromatography using silica, eluen used ethylacetate : methanol in SGP. Test the purity of the insulation is done with KLT and melting point. Flavonoids obtained pure white-brownish powder with melting point range 263,3-263,8 0C. Test result with 10% NaOH color reagents, concentrated H2SO4 andMg-HCl showed the presence offlavonoids. Results test KKt2A bares stain is at regional aglikon flavon. The data analysis spectra IR showed the groups –OH ether, C=C aromatis and carbonyl C=O. While of spectra uv-vis the presence of a cluster of -OH on C-3. From the data up allegedly flavonoid the result of isolation is a flavone with a cluster of –OH on C-3 namely 3-hidroksiflavon.